Reconstruction of Criminal Sanction and Rehabilitation Combating On Narcotic’s Victims Based On Religious Justice - Carto Nuryanto (Law Development Journal, 2019)
During this time, law enforcement officials tend to impose criminal sanctions for victims of drug without rehabilitation but instead provide criminal sanctions such as prison. Without the detoxification process through medical and social rehabilitation process, they will soon be back looking for narcotics so out of prisons because of the association in the increasingly severe prison, As described in Act No. 35 of 2009 on Narcotics Article 54 that the rehabilitation of abusers of Narcotics; â€œAddicts Narcotics and Narcotics abuse on victims to undergo mandatory medical rehabilitation and social rehabilitationâ€. It is strengthened by the Supreme Court Circular No. 04 of 2010 concerning the Placement, Victims and Narcotic Addict Into The Rehabilitation Institute of Medical and Social Rehabilitation. Because of their position in this case is the victim, not the dealer let alone active users is appropriate that they get special treatment before the law. Law enforcement officials are supposed to be representatives of God on earth to be a judge and establishing the truth, fairest, it erred in sentencing. Besides religiously also does not reflect the nature of God's servants who are wise and fair.Keywords: Reconstruction; Sanctions; Narcoticâ€™s Victim; Religious Justice.